AN ANALYSIS OF ENGLISH LANGUAGE LEARNING TOWARD ENTREPRENEURSHIP EDUCATION FOR SANTRI IN PONDOK PESANTREN SLEMAN YOGYAKARTA - Rahayu Rahayu (INOVISH JOURNAL, 2020)
Entrepreneurship education in Islamic Boarding Schools (Pondok Pesantren) is still growing in certain areas in various parts of Indonesia. According to data from Ministry of Religious Affairs Yogyakarta (2018), there are 288 Islamic Boarding Schools (Pondok Pesantren) in the Special Region of Yogyakarta. Although some Islamic boarding schools (Pondok Pesantren) still implement education traditionally and only in the form of religious education, some of them are already modern enough to introduce the importance of learning English to their santri. This study uses a qualitative descriptive approach, which produces descriptive data in the form of written or oral words from people and observable behavior. This approach is directed towards the background and the whole individual. The first step is profiling all Pondok Pesantren in Sleman Regency. Then Pondok Pesantren Nawesea is selected because it has an area of excellence in English curriculum with various learning activities using English language. After collecting data and visiting Pondok Pesantren Nawesea, several conclusions and description were drawn and it influenced the implementation of English learning in the entrepreneurship education. The next step is to make observations about the understanding of students toward entrepreneurial competencies in enterprenurship education in Pondok Pesantren Nawesea. Regarding the result of the study, the researcher concludes that it is undeniable that Pondok Pesantren Nawesea (Nawesea Islamic boarding school) has an excellent implementation of English language learning for students, especially for its language intensive programs. The other main objective soon to be developed is to implement entrepreneurial competencies of santri in Pondok Pesantren Nawesea. The data from the observations of this research shown that the closest step that can be taken is to build Kopontren (Kooperasi Pesantren) in which the management activities can involve independent students (santri mandiri) in Pondok Pesantren Nawesea.